Деякі питання дотримання права на захист у досудовому розслідуванні - Гловюк Ірина Василівна; Гловюк Ирина Васильевна; Glovyuk Iryna V. (My University, 2017)
Стаття присвячена дослідженню проблем дотримання права на захист у досудовому розслідуванні. На основі аналізу практики ЄСПЛ, положень КПК, судової практики доведено, що невручення слідчим або прокурором, що здійснює нагляд за додержанням законів під час проведення досудового розслідування, копії клопотання про продовження строку досудового розслідування підозрюваному та його захиснику є порушенням права на захист, засади розумності строків і змагальності сторін, свободи в поданні ними суду своїх доказів і у доведенні перед судом їх переконливості.

Статья посвящена исследованию проблем соблюдения права на защиту в досудебном расследовании. На основе анализа практики ЕСПЧ, положений УПК, судебной практики доказано, что невручение следователем или прокурором, осуществляющим надзор за соблюдением законов при производстве досудебного расследования, копии ходатайства о продлении срока досудебного расследования подозреваемому и его защитнику является нарушением права на защиту, принципов разумности сроков и состязательности сторон, свободы в представлении ими суду своих доказательств и в доказывании перед судом их убедительности.

The article is devoted to the analysis of issues of observance of the right to defense at pre-trial proceedings. On the basis of analysis of ECHR practice, provisions of Criminal Procedural Code of Ukraine, judicial practice, it is proved that not serving a copy of motion to extend time limits of pre-trail investigation on suspect and his defense counsel by investigator or prosecutor who supervises the compliance with law in the course of the pre-trial investigation is a violation of right to defense, principle of reasonable time and adversary and freedom to present their evidence to the court and prove the preponderance of evidence before the court as in that case defense finds itself at a disadvantage compared to prosecution. Not serving a copy of the motion on suspect and his defense council by investigator or prosecutor who supervises the compliance with law in the course of the pre-trial investigation should bring criminal sanctions with it in the form of repealing the decision and to declare all pieces of evidence inadmissible that were collected after extending time limits of a pre-trail investigation. Extending the limits of a pre-trail investigation may require changing the defense tactics. It is stated that during a trial defense counsel should make a motion for declaring all pieces of evidence inadmissible that were collected after extending time limits of a pre-trail investigation in case of not serving or delayed serving a copy of the motion on suspect and his defense counsel by investigator or prosecutor who supervises the compliance with law in the course of the pre-trial investigation.
Гловюк І. В. Деякі питання дотримання права на захист у досудовому розслідуванні / І. В. Гловюк // Вісник кримінального судочинства. – 2017. - №2. – С. 33-39.
Keywords: захист; змагальність; прокурор; строк досудового розслідування; клопотання; защита; состязательность; прокурор; срок досудебного расследования; ходатайство; defense; adversary; prosecutor; time limits of pre-trail investigation; motion